Assessment of the Development of Legal Regulation on the Protection of Major Accidents - Bleszity, János; Kátai-Urbán, Lajos (Magyar Rendészet, 2016)
Hungarian regulations on industrial safety are based on the legal and institutional system for the protection of major industrial accidents involving dangerous substances. The aim of this article to overview the measures related to the development of the legislative area for industrial safety and the supervision of dangerous establishments, and also to draw conclusions of this progress.